Gender-Based Violence on the X (Twitter) Platform: A Digital Criminological Analysis in the Social Media Era - Amatul Kafi Yasmeen; Asri Dewi Pratiwi; Zaskia Sharefa Kautsar; Nila Puspita Sari; Lidya Kristanti; Nur Baeti Aprilianti; Aneira Jasmine; Aurelia Ramadhani; Ikhsan Putra Ramadhan; Valesca Angelina Pardede; Halimah Halimah; Runi Sikah Seisabila (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The rapid growth of social media, particularly the X (Twitter) platform, has expanded opportunities for public interaction and freedom of expression while increasing the prevalence of online gender-based violence (OGBV). This study examines users' perceptions of gender-based violence on X, identifies the factors contributing to its occurrence, and analyzes its impacts from a digital criminological perspective. Using an empirical qualitative descriptive approach, data were collected through an online questionnaire administered to 50 active X users. The findings reveal that user anonymity is the primary factor facilitating gender-based violence, accompanied by weak content moderation, limited digital literacy, poor online communication ethics, and the rapid dissemination of harmful content. Respondents frequently encountered verbal harassment, sexist and misogynistic comments, cyberbullying, doxxing, body shaming, victim blaming, and threats of sexual violence. These findings support the Online Disinhibition Effect, which explains how anonymity encourages aggressive online behavior, and Routine Activity Theory, which emphasizes the interaction between motivated offenders, suitable targets, and inadequate guardianship in facilitating cyber-enabled victimization. The study recommends strengthening content moderation, improving reporting mechanisms, enhancing digital literacy, enforcing legal protections, and promoting gender equality campaigns to create safer and more inclusive digital environments.